Secondhand lions - McCanlies, Tim.; Duvall, Robert; Caine, Michael; Osment, Haley Joel, 1988-; Sedgwick, Kyra.; New Line Home Entertainment (Firm) ([United States] : New Line Home Entertainment, 2004)
To the rest of the world, Garth and Hub are mysterious old men hiding millions. But to Walter, they are family - and now they're about to lead him on an adventure he'll never forget.
Released as a motion picture in 2003.
Special features: widescreen and fullscreen versions; deleted/alternate scenes with optional filmmaker commentary; on the set with "Secondhand Lions"; Haley Joel Osment: an actor comes of age; visual effects comparisons; filmmaker commentary with the director; theatrical trailer and TV spots.
Executive producers, Janis Rothbard Chaskin, Kevin Cooper, Toby Emmerich, Mark Kaufman, Karen Loop ; original music by Patrick Doyle ; cinematography by Jack N. Green ; film editing by David Moritz.
Robert Duvall, Michael Caine, Haley Joel Osment, Kyra Sedgwick.
MPAA rating: PG.
DVD.
Keywords: Uncles -- Texas -- Drama; Bildungsromans -- Drama; Family -- Drama; Texas -- Drama; Films for the hearing impaired; Feature films